2011
DOI: 10.1159/000329177
|View full text |Cite
|
Sign up to set email alerts
|

Treating Anxiety in Patients with Coronary Heart Disease: A Randomized Controlled Trial

Abstract: Background: Anxiety is frequent in patients with coronary heart disease (CHD) and influences the course of the disease, but no randomized controlled trial has investigated the effects of a psychotherapy intervention in CHD patients with elevated anxiety scores. The main aim of this study was to evaluate the effects of a 6-month psychotherapy intervention on anxiety in this group of patients. Methods: Fifty-two patients (61 ± 8.0 years, 14 female) with CHD and elevated levels of anxiety completed the study afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 50 publications
0
27
0
4
Order By: Relevance
“…For the majority of studies (93 studies, out of 119), the inclusion criteria did not specifically include a psychiatric diagnosis of an anxiety disorder. Of the remaining 26 studies, 4 included elevated anxiety in their inclusion criteria (30, 31, 39, 43), 9 included patients with anxiety and/or depression (44-52), 8 included patients with depression, depressive symptoms, or mood disorder only (36, 37, 40, 53-57), 3 included patients with ‘distress’ (10, 58, 59), one included patients with “psychosomatic symptoms” including restlessness, anxiety, altered mood, and insomnia (60), and another included patients with “exhaustion” (61).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the majority of studies (93 studies, out of 119), the inclusion criteria did not specifically include a psychiatric diagnosis of an anxiety disorder. Of the remaining 26 studies, 4 included elevated anxiety in their inclusion criteria (30, 31, 39, 43), 9 included patients with anxiety and/or depression (44-52), 8 included patients with depression, depressive symptoms, or mood disorder only (36, 37, 40, 53-57), 3 included patients with ‘distress’ (10, 58, 59), one included patients with “psychosomatic symptoms” including restlessness, anxiety, altered mood, and insomnia (60), and another included patients with “exhaustion” (61).…”
Section: Resultsmentioning
confidence: 99%
“…Ten interventions primarily involved forms of cognitive-behavioral therapy (CBT) (47, 48, 54, 55, 90-92). Two of these CBT-focused studies also provided stress management training (53, 93) and one included antidepressant medication (68); eight involved skills training such as problem-solving and self-management strategies (10, 36, 61, 62, 94-97); three studies provided social support or ‘mentorship’ to patients (38, 98, 99), two provided psychotherapy (30, 100); and one involved future care planning and related counseling (65). One offered patients a choice between problem solving counseling, antidepressant therapy, or both (37).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently updated Cochrane review assessed the efficacy of psychological interventions in CHD patients compared with usual care (Richards et al, 2017). Although this review did not report effects for CBT specifically, we calculated the effect size across those reviewed studies that evaluated interventions based on CBT and that reported outcomes for depression and/or anxiety (Burgess et al, 1987; Black et al, 1998; Berkman et al, 2003; Claesson et al, 2005; McLaughlin et al, 2005; Michalsen et al, 2005; Koertge et al, 2008; Freedland et al, 2009; Merswelken et al, 2011; Turner et al, 2012, 2014; O'Neil et al, 2015). Again, effect sizes were small: 0.29 and 0.24 for anxiety and depression, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that anxiety is a risk factor for MI, very few treatment studies on anxiety in patients with a recent MI have been conducted [ 11 ]. To our knowledge, there is only one randomized controlled clinical trial (RCT), which showed no effect of the intervention [ 13 ]. There are several studies that have used group-based interventions focusing on a broader range of psychosocial risk factors with good results.…”
Section: Introductionmentioning
confidence: 99%